FAKTOR YANG BERHUBUNGAN DENGAN IDWG DAN TEKANAN DARAH PASIEN HEMODIALIS DI RUMAH SAKIT SWASTA YOGYAKARTA - Th Tatik Pujiastuti (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Patients with hemodialysis always increase every year. In Indonesia the number of active hemodialysis in 2016 increased by 72.29% from 2015. The success of hemodialysis can be seen from the clinical condition of the patient, especially Interdialitic Weigh Giant (IDWG) and blood pressure. Therefore, it is very important to study related factors to IDWG and blood pressure in hemodialysis patients. Objective: This study aims to describe related factors to IDWG and blood pressure in hemodialysis patients. Methods: This is a quantitative descriptive analytic research. Number of samples is 65 hemodialysis patients using random technique. Result: Based on the Spearman correlation test showed that statistically, there is a correlation between gender and IDWG p 0,024 < 0,05, Exercise and Intradialysis diastolic blood pressure with p 0,000 <0,05 (r = 0,46), comorbidities with Intradialysis diastolic blood pressure p 0,000 < 0,05 and fluid intake with intradialysis systolic blood pressure p 0,031 <0,05 (r = 0.28). Conclusion: It is assumed that gender, exercise, comorbidities and fluid intake are related to IDWG and blood pressure. Based on result of this study, this is important for nurses to take more intensive education about controlling cimorbidities, fluid intake and motivation to exercise in daily life. Keywords: Hemodialysis, blood pressure, Interdialitic Weigh Giant (IDWG)